An Alternative Way in Overcoming Global Crisis: Information Acquiring in the Social Capital and Capacity Usage - Sağsan, Mustafa; Yücel, Recep; Sözen, Cenk (Information World, 2010)
Intellectual capital, intangible assets of an organization mobilizing the resources it provides long-term life and do not appear in the balance sheet as assets as defi ned, information is based on a new type of capital. Patents and trademarks of the organization has received the organization’s reputation, customer loyalty, such as abstract elements, in other words, information, and such assets are shown as are the basis of the capital. These assets, intellectual capital is separated into three basic components. The fi rst, is the human capital and employee organizations of past experience, business skills refers to. Second, structural capital and the organization’s culture and structure had settled into the habit of doing business and professionalism includes. Third, the relational or social capital and intellectual capital is the most important component. This type of capital, do business with organizations around the connection with other organizations that is based on. A social network, this mechanism contained in the bonds of members based on their capacity utilization means that they created. Actors within this network mechanism, the organization itself or the units can take an active role. This study, to companies aff ected by the global crisis, the crisis of social capital as a way out of a capacity to off er tips and suggestions for how could be increased. For this reason, study, an alternative approach as a means fi rms can exit from the crisis of social networking mechanism for how confi gurations and relational capital, how and in what form of action needed, the basic problematically respectively.
Keywords: Intellectual capital; Social capital; Social networking mechanism; Global crisis